Effects of cooking on toxins levels and influence of food additives on toxins level in food products - Theng, C. Y.; Jualang Azlan Gansau (hibiscus publisher, 2014)
Cooking is a process that could reduce the contamination level of toxic chemicals such polyaromatic hydrocarbons (PAHs) in several foodstuffs. However, this effect depends largely on the cooking process (grilling or frying), cooking material selection (charcoal, gas or wood), type of toxicant and the specific food item. This review discussed in detail pertaining to the effect of cooking and addition of food additives on the toxicant levels in foodstuff.